Philosophy of Education: A Theoretical Study of Concepts, Schools, and Their Influence in Educational Science: Filsafat Pendidikan: Kajian Teoritis tentang Konsep, Aliran, dan Pengaruhnya dalam Ilmu Pendidikan - Asmi Astuti; Farika Istiana; Wedi Iswandi; Afriend Yudisman; Linna Marleni; Merri Sri Hartati; Susiyanto Susiyanto (Indonesian Journal of Innovation Multidisipliner Research, 2025)
Philosophy of education is a branch of philosophy that reflects the nature, goals, and methods of education in understanding the basic principles that shape the education system. This study includes various theories in epistemology, ethics, and ontology that play a role in formulating policies, curricula, pedagogical practices, and effective teaching methods. Education aims to develop the intellectual, emotional, social, and spiritual potential of individuals through a lifelong learning process. With a library research approach, this article discusses the relationship between philosophy of education and educational science, branches of philosophy, and the influence of philosophical schools on the development of the education system. Understanding the philosophy of education is very important for educators and policy makers in creating a better education system. In addition, the philosophy of education contributes to building a humanistic education system that focuses on the development of the intellect, morality, and character of students for the advancement of society.